1988
DOI: 10.1177/030098588802500605
|View full text |Cite
|
Sign up to set email alerts
|

Lesions in Brangus Cattle with Chediak-Higashi Syndrome

Abstract: Abstract. Hair, peripheral blood leukocytes, and other tissues from two related Brangus calves with phenotypic characteristics of Chediak-Higashi syndrome were examined by light and electron microscopy. Enlarged, pleomorphic, cytoplasmic granules, morphologically compatible with lysosomes, were seen in several neutrophils, many eosinophils, renal tubular epithelial cells, and Kupffer cells. Hair shafts of the calves showed irregular distribution and clumping of melanin granules. Severe infection and a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…The lower platelet aggregation rate induced by collagen and the larger sized and less numbered granules in eosinophils observed in all cases in this study were in agreement with those in Japanese Black cattle with δ-SPD reported previously [1]. These findings were also reported in cattle with CHS [2,5,18,19,26], which was one of diseases belonged to δ-SPD in cattle. Affected Hereford cattle and Brangus cattle are reported to have shown partial albinism of hair coat and iris, marked suceptibility to infections and photophobia [2,5,19], but those were not observed in any of the cases in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lower platelet aggregation rate induced by collagen and the larger sized and less numbered granules in eosinophils observed in all cases in this study were in agreement with those in Japanese Black cattle with δ-SPD reported previously [1]. These findings were also reported in cattle with CHS [2,5,18,19,26], which was one of diseases belonged to δ-SPD in cattle. Affected Hereford cattle and Brangus cattle are reported to have shown partial albinism of hair coat and iris, marked suceptibility to infections and photophobia [2,5,19], but those were not observed in any of the cases in this study.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were also reported in cattle with CHS [2,5,18,19,26], which was one of diseases belonged to δ-SPD in cattle. Affected Hereford cattle and Brangus cattle are reported to have shown partial albinism of hair coat and iris, marked suceptibility to infections and photophobia [2,5,19], but those were not observed in any of the cases in this study. Therefore, the cases and those cattle examined in our previous report [1] were unlikely classified in CHS.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In most human patients affected with CHS, death often occurs in the first decade of life due to infection, bleeding, or development of the 'accelerated phase', which is characterized by a lymphoproliferative syndrome with lymphohistiocytic infiltration. CHS in cattle is found in Hereford [49], Japanese Black [69] and Brangus breeds [2]. In Japan, Japanese Black cattle affected with CHS are frequently seen in South Kyusyu area (Miyazaki and Kagoshima Prefectures) [46] and infrequently in other places.…”
Section: Characteristics Of Chediak-higashi Syn-dromementioning
confidence: 99%
“…Prolonged bleeding time has been reported in most of affected animal species [2,5,6,12,16,35,46,63]. On the other hand, coagulation system is normal in humans, Japanese Black cattle and cats affected with CHS [12,35,46].…”
Section: Characteristics Of Chediak-higashi Syn-dromementioning
confidence: 99%